STRATEGIC DIRECTIONS FOR ENSURING THE STABLE FUNCTIONING OF AGRIBUSINESS ENTERPRISES AND RURAL AREAS IN THE CONTEXT OF POST-WAR RECOVERY OBJECTIVES - TITOV, Denys; OKHOTA, Yuliia; CHIKOV, Illia; DOTSIUK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the strategic directions for ensuring the stable functioning of Ukraine’s agribusiness sector and rural territories under conditions of sharp external volatility caused by the combination of military risks, economic shocks, and climate change. Based on a comprehensive analysis of the key challenges of 2024-2025 including disruptions of production cycles due to hostilities, logistical constraints, rising resource costs, labour shortages, and regulatory instability the study substantiates the need for agricultural enterprises to transition toward adaptive and flexible development models. Data from the FAO, the World Bank, national statistics, and contemporary scientific research are used to identify transformation trends within the agricultural sector, assess the scale of losses, and construct a systemic understanding of how crisis factors affect the production and financial resilience of agribusiness.The study formulates a system of strategic directions aimed at restoring and strengthe ning the resilience of the agricultural sector. These include diversification and flexibility of production models, the implementation of digital technologies and precision farming, process automation, the development of new financial instruments (such as agricultural receipts, commodity derivatives, crop insurance, and portfolio guarantees), the strengthening of rural communities and cooperative structures, as well as ecological and climate adaptation. Special attention is given to post-war priorities that will determine the sector’s development trajectory in the medium term: demining and returning agricultural land to productive use, the reconstruction of critical infrastructure (grain storage facilities, irrigation systems, and logistics routes), the modernization of state financial support mechanisms, and the creation of favourable conditions for attracting private investment. Based on these components, the paper proposes the model «Resilient Agribusiness Enterprise 2030» which outlines key parameters of future development, including increased processing capacity, growth in energy autonomy, expanded insurance coverage, deeper digital integration, and enhanced socio-economic resilience of rural territories.